Staphylococcus aureus Infection Influences the Function of Intestinal Cells by Altering the Lipid Raft-Dependent Sorting of Sucrase–Isomaltase - Mergani, AhmedElmontaser; Wanes, Dalanda; Schecker, Natalie; Branitzki-Heinemann, Katja; Naim, Hassan Y.; von Köckritz-Blickwede, Maren (Frontiers in Cell and Developmental Biology, 2021)
Staphylococcus aureus is an important nosocomial and community acquired facultative pathogen. Many studies have reported that S. aureus infections are associated with intestinal symptoms, but little is known about the molecular mechanisms implicated in S. aureus-induced alterations of intestinal functions. In this study, we investigated the implication of lipid rafts in the interaction of S. aureus with Caco-2 cells. To assess potential alterations in the lipid raft structure and effects on the hydrolytic function we utilized sucrase isomaltase as the major intestinal α-glucosidase that is associated with and sorted to the apical membrane via lipid rafts. Seven days post-confluent Caco-2 cells were infected with S. aureus Newman and further incubated for additional 2 days. After 48h the levels of SI expression as well as the enzymatic function of this protein were assessed in the infected versus non-infected cells. Analysis of the sorting behavior of SI to the apical membrane constituted another crucial aspect in studying the effects of S. aureus on Caco-2 cells. For this purpose, the apical or brush border membranes (BBM, referred to as P2 fraction) were separated in both infected and non-infected cells from the basolateral and intracellular membranes (referred to as P1 fraction) by employing a cationic-based procedure using CaCl2. The data show that there is no significant change in the overall expression levels of SI in the infected versus the non-infected cells as assessed by Western blot analysis using monoclonal anti-SI antibodies. By contrast, a significant decrease in the localization as well as the specific hydrolytic activities of SI towards sucrose and isomaltose (palatinose) was observed in the brush border membrane (P2 fraction) in Caco-2 cells 48h post-infection. Concomitantly, the specific SI activities increased in the basolateral membrane/intracellular fraction (P1). Noteworthy, the specific activity of SI in the brush border membrane of infected cells was markedly reduced as compared to their non-infected counterparts. The data accumulated from this study strongly suggest that infections with S. aureus influence the final step in the lipid rafts-associated trafficking of human SI fand thereby may trigger secondary functional gastrointestinal disorders.